Systemic IL-1&beta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Periodontaldisease,a commoninflammatoryoraldiseaseinvolvedperiodontaltissues,has beenlinked with the evidenceof some systemicdisorders. Recently,periodontaldisease has beensuspected as a trigger of systemic disorders. Penetration of bacterial products, such as lipopolysaccharide (LPS)may reach into deeper periodontal tissues. Therefore there may affect-systemic blood and cytokines production. Interleukin-1~ (IL- 1~) and Tumour Nuclear Factor-a (TNF-a) are known as pro-inflammatory cytokines. The production of systemic IL-1~and TNF-aof E.coli lipopolysaccharide-induced periodontitis model on rats was investigated in this research. Fifteen male Wistar rats, aged 6-8 weeks used for this study were divided into 3 groups. For group 1 and 2, silk ligature 3/0 were inserted in interdental area between upper right molar 1 and 2. Firstand second group received solution containing lOllg/ml and 1mg/ml E.colilipopolysaccharide, respectively, mixed with 2%carboxymethylcellulose (CMe)diluted in lOO1l1of phosphate buffer saline (PBS).The solution was topically applied on gingivaltissues around the gingival sulcus, a single topical application of solution once per 2 days for 14 days. Untreated subjects were used as negative control. Onday 15, the blood was collected from vena orbitalis, and rats were sacrificed. The blood serum of each group was divided into 2 groups and cultured for 4 hours with or without 20111of 100ng/ml of E. coli LPS.ELISAtechniques were used to measure the cytokine productions of the supernatant. The data was ana lysed using Repeated Measure ANOVA.Jhis study showed that there was a significantincrease of IL-1~productionon low dose of LPScompared to control and high dose of LPSgroups (p